Language and culture on the margins : global/local interactions - Kroon, Sjaak; Swanenberg, Adrianus Petrus Cornelis, 1968- (New York, NY : Routledge, Taylor & Francis Group, 2018)
"This collection of thirteen essays examines sociolinguistic phenomena in a wide variety of marginal environments, providing both an overview of globalizaiton on the margins and a foundation for an expanded understanding of the processes of linguistic and cultural changes at work in these settings. Taking an expansive conceptual view of margins, the volume is organized in three parts, looking at examples of marginal spaces in the nation-state, in online environments, and in the peripheries of urban locations, globally to call attention to new and changing discursive genres, patterns, practices, and identities emerging in these spaces as a result of contemporary mobilities, the evolving global economy, and socio-political changes. With previous research previously confined to the study of globalization in urban areas, this volume opens the door for further research on the complex sociolinguistic processes resulting from globalization on the margins, making this an ideal resource for students and scholars in sociolinguistics, globalization and heritage studies, new media, anthropology, and cultural studies"--
Introduction : language and culture on the margins / Sjaak Kroon and Jos Swanenberg -- Redefining the sociolinguistic "local" : examples from Tanzania / Jan Blommaert -- Reterritorialization and the construction of margins and centers through imitation in Indonesia / Zane Goebel -- English in Asmara as a changing reflection of online globalization / Sjaak Kroon, Jenny-Louise Van der Aa and Yonas Mesfun Asfaha -- Gender performativity in virtual space : transglossic language practices of young women in country Bangladesh / Shaila Sultana -- The language and culture of New Kids : appreciation of and familiarity with online Brabantish identities / Jos Swanenberg -- Literacy acquisition and mobile phones in a South African township : the story of Sarah / Fie Velghe -- Scaling queer performativities of genders and sexualities in the periphery of Rio de Janeiro in digital and face-to-face semiotic encounters / Luiz Paulo Moita-Lopes, Branca Falabella Fabrício and Thayse Figueira Guimarães -- Expanding marginality : linguascaping a Transcarpathian spa in south-western Ukraine / Petteri Laihonen and István Csernicskó -- Globalized linguistic resources at work : a case study of a local supermarket in Finnish Lapland / Massimiliano Spotti -- Calypso music, globalization and plurilingualism in the Dutch Caribbean / Gregory Richardson -- Consuming English in rural China : lookalike language and the semiotics of aspiration / Xuan Wang.
Includes bibliographical references and index.
ENH
Parama Publishers
Keywords: Linguistic minorities; Sociolinguistics; Marginality, Social